SIPD User Satisfaction In The North Sumatra Regional Government Using The Delone And Mclean Model Approach - Anggi Pratama Nasution; Irawan Irawan (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
The purpose of this study is to examine the satisfaction of SIPD users using the DeLone and McLean Model Approach. The DeLone and McLean Model is used to analyze how information systems contribute to increasing SIPD user satisfaction. Data were collected through a survey using a questionnaire instrument aimed at local government employees in North Sumatra. The data analysis technique applied was the PLS structural equation model (SEM-PLS). The findings of this study indicate that the quality of the information system has a statistically significant influence on SIPD user satisfaction. Perceived usefulness influences SIPD user satisfaction. Perceived usefulness influences SIPD user satisfaction. The implications of the results of this study indicate that the Quality of the Information System and Perceived Usefulness have a significant impact on SIPD User Satisfaction, so there are several important implications both in the context of theory and practice..